Development of Tuna Fish (Thunnus Sp) in Increasing Hemoglobin Levels for Pregnant Women at the Waisai Health Center, Raja Ampat Regency - ., Sunaeni; Egam, Adriana; Kundarti, Finta Isti; Sari4, Catur Anita (South Eastern European Journal of Public Health, 2024)
Introduction: Based on Riskesdas 2018, the prevalence of anemia in pregnant women increased from 37.1% (2013) to 48.9% (2018). Iron deficiency during pregnancy can inhibit fetal development and have an impact on the quality of pregnancy outcomes, including the risk of BBLR, stunting, and abortion. At the Waisai Health Center, 36.36% of pregnant women experience anemia. Protein has an important role in providing organic iron (haem), and tuna is a high source of protein. Sorong, as one of the tuna-producing regions in Indonesia, offers great potential for food innovation. Objective: This study aims to develop processed tuna fish (Thunnus Sp Cookies) to increase Hb levels of pregnant women. Method: The research lasted for two years (January 2021-December 2022). The first year was focused on identifying the best formula of Thunnus Sp Cookies through a panelist test using the ANOVA method. The second year, using a pre and post experiment control group design, examined the effect of tuna cookies on the Hb level of pregnant women. The sample was 44 pregnant women, with data analyzed using the paired T-test. Results: The results of this research support the roadmap of the Sorong Ministry of Health Polytechnic (2019-2023) in the development of appropriate technology based on local culture. The first year's output is in the form of a monograph book draft, while the second year produces ISBN books and articles in nationally accredited journals as well as publication drafts in international journals. The level of technological readiness reaches level 3, namely the Thunnus Sp Cookies formula application.